Information and Communications Technology Penetration and Environmental Sustainability in Sub-Saharan Africa - Cosmas, Ambe; Wisdom, Okere; Emmanuel, Ajayi Olusuyi; Oladotun, Mabinuori; Adeyinka, Badmus Dauda; Shola, Ogunmola Adekunle; Eniola, Aladegoroye Idris (International Journal of Economics and Financial Issues, 2025)
Africa’s information and communications technology (ICT) expansion, especially in mobile phone use, has been substantial; nonetheless, it falls behind in internet accessibility and has environmental sustainability issues, such as climate change and pollution. This study investigates the nexus between ICT penetration and environmental sustainability in Sub-Saharan Africa, using data from the World Bank and utilising a Panel Generalised Method of Moments analysis. Research demonstrates that ICT, as seen by mobile phone utilisation, positively correlates with CO2 emissions in Sub-Saharan Africa. ICT has opportunities to promote environmental sustainability via creative solutions, such as mobile money systems and energy-efficient technologies. The research highlights the need to tackle infrastructural and cost issues, advance national ICT efforts, and implement sustainable practices, such as energy-efficient hardware and life-cycle asset assessments. Policymakers are urged to use ICT as a strategic instrument to address environmental concerns and attain sustainability in the area.